(3Gdeaghe (B- (3GdLhGfH GdGSGSjI (B- (3GdQYGjI (B- (3GdGcJTGa (B- (3GdUdGMjI GdMQcjIs - (3MSf Rcj eMeO eMeOs ((3GdGScfOQjIs (3GdecJHI GdeUQjI ddWHGYI h GdfTQ h GdJhRjYs, 2002)
(3GdeJahbhf GdQjGVjhf h JWhQ GdeLGdGJ GdJWHjbjI h GdJYdjejI h GdJOQjHjI h Cge GdfhGMj GdYdGLjI GdQjGVjI GdeJUdI HeeGQSI GdCfTWI GdQjGVjI, ShGA cGf Pdc aj GdCfTWI h GdCdYGH GdaQOjI Ch GdLeGYjI(B.s
Keywords: (3GdWdGH GdehghHhf(B_(3GdJQHjI GdNGUIs